The Effect of the 5E Model on Jordanian EFL Fifth-Grade Students' Reading Comprehension Skills - Alshwayat, Rania Mohammad; Hijazi, Dima Ali (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to examine the effect of the 5E Model on Jordanian EFL fifth-grade students’ reading comprehension skills. Methods: The study uses a quasi-experimental design based on two groups (one experimental and one control group). The outcome of the students' post-test in the chosen reading comprehension skills is the dependent variable, while the 5E instructional model is the independent variable. Results: The results show that the 5E Model improved students' understanding of what they were reading. In light of the findings of the current study, the researchers suggest adopting the 5E Model to help students with their reading comprehension. Conclusions: The current study set out to determine how the 5E Model affects the reading comprehension of Jordanian fifth-grade participants. To achieve this, a ‘5E model’-based educational program was designed and put into place for the academic year 2023–2024. Students' reading comprehension increased after the 5E Model was put into practice.